Nutrition labelling: a review of research on consumer and industry response in the global South - Jessie Mandle; Aviva Tugendhaft; Julia Michalow; Karen Hofman (Taylor & Francis Group, 2015)
Background: To identify peer-reviewed research on consumers' usage and attitudes towards the nutrition label and the food industry's response to labelling regulations outside Europe, North America, and Australia and to determine knowledge gaps for future research. Design: Narrative review. Results: This review identified nutrition labelling research from 20 countries in Asia, Africa, the Middle East, and Latin America. Consumers prefer that pre-packaged food include nutrition information, although there is a disparity between rates of use and comprehension. Consumer preference is for front-of-pack labelling and for information that shows per serving or portion as a reference unit, and label formats with graphics or symbols. Research on the food and beverage industry's response is more limited but shows that industry plays an active role in influencing legislation and regulation. Conclusions: Consumers around the world share preferences with consumers in higher income countries with respect to labelling. However, this may reflect the research study populations, who are often better educated than the general population. Investigation is required into how nutrition labels are received in emerging economies especially among the urban and rural poor, in order to assess the effectiveness of labelling policies. Further research into the outlook of the food and beverage industry, and also on expanded labelling regulations is a priority. Sharing context-specific research regarding labelling between countries in the global South could be mutually beneficial in evaluating obesity prevention policies and strategies.